Treatment of Distal Aneurysms of the Cerebellar Arteries by Intraaneurysmal Injection of Glue - Cognard, Christophe; Weill, Alain; Tovi, Metin; Castaings, Lina; Rey, Alain; Moret, Jacques (American Journal of Neuroradiology, 1999)
Summary: Distal aneurysms of the cerebellar arteries are associated with a poor prognosis, as surgery or embolization with GDCs is very difficult. We report our experience with a new therapeutic method involving intraaneurysmal injection of glue. Three aneurysms were catheterized with a flow-guided microcatheter, and glue was slowly injected into the aneurysms. In two cases, treatment resulted in total occlusion of the aneurysm with preservation of the parent artery. In one case, the aim was to occlude both the aneurysm and parent artery.